STRATEGI PARTAI DEMOKRASI INDONESIA PERJUANGAN KABUPATEN KLUNGKUNG DALAM MENINGKATKAN DUKUNGAN KONSTITUEN - Simanjuntak, Tomy Wirawijaya; Pramana, Gede Indra; Puspitasari, Ni Wayan Radita Novi (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
The research seeks to find out the political strategy used by the PDI-Perjuangan in Klungkung Regency in creasing constituent support after failing to win the 2014 election so that in the 2019 election, PDI-Perjuangan can dominate the number of votes in Klungkung Regency.. This research using qualitative method with descriptive type of analysis. This research uses theory of political strategy by Peter Schroder who recognizes a defensive strategy and an offensive strategy. The results of this study show that defensive strategy by PDI Perjuangan in Klungkung Regency is changing the way to embraces their support base, increasing transparency, involving all parts of the party and going directly to touch with constituents. Offensive strategy is carried out by forming bodies within the party, involving wing organizations and creating programs that can reach all their constituents. By implementing this defensive and offensive strategy, PDI-Perjuangan of Klungkung Regency, which in the 2014 election won 25,591 (21.85%) out of a total of 117,140 votes, was able to dominate the number of votes in Klungkung Regency in the 2019 election with a 38,890 (31.28%) votes. out of 124,272 valid votes.